Effects of most-probable-number method and plate count method on fungal population density at different pH of assay medium - Bhowmik, Subrata Nath (Bangladesh Journal of Botany, 2018)
The most-probable-number method was adopted to evaluate population density of fungus using two fungal models in potato-dextrose media of pH 5.6 and 3.5. The results were compared with plate count methods. Concentration of propagules ranged of 6.11 - 6.55 log cfu/ml in Rhizopus), 6.01 - 6.09 log cfu/ml in Trichoderma at pH 5.6 and 6.68 - 6.75 log cfu/ml (Rhizopus), 6.10 - 6.32 log cfu/ml (Trichoderma) at pH 3.5. The order of results was - most-probable-number > spread plate> pour plate. Population density was relatively higher at pH 3.5 and no significant differences (p ≤ 0.05) among the methods recorded.